2017
DOI: 10.1155/2017/6516854
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Immunomodulation Properties of Mesenchymal Stromal Cells: A New Insight into the Role of ICAM-1

Abstract: Mesenchymal stromal cells (MSC) control excessive inflammation and create a microenvironment for tissue repair protecting from chronic inflammation and tissue fibrosis. We examined the molecular mechanisms of MSC immunomodulatory function in mixed cultures of human adipose-derived MSC with lymphocytes. Our data show that MSC promote unstimulated lymphocyte survival potentially by an increase in antigen presentation. Under inflammatory conditions, mimicked by stimulation of TCR in lymphocytes, MSC suppress acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 43 publications
3
43
0
Order By: Relevance
“…The adhesion molecules ICAM-1 and VCAM-1 regulate the migration of MSCs and provide their interaction with co-operating immune cells, making them indispensable for MSC-mediated immunosuppression [42,43]. Similar to other reports [18], we failed to observe single VCAM-1 bearing ASCs, found mostly single positive ICAM-1 cells and, less frequently, cells co-expressing both of these molecules (Figure 2A).…”
Section: Discussionsupporting
confidence: 88%
“…The adhesion molecules ICAM-1 and VCAM-1 regulate the migration of MSCs and provide their interaction with co-operating immune cells, making them indispensable for MSC-mediated immunosuppression [42,43]. Similar to other reports [18], we failed to observe single VCAM-1 bearing ASCs, found mostly single positive ICAM-1 cells and, less frequently, cells co-expressing both of these molecules (Figure 2A).…”
Section: Discussionsupporting
confidence: 88%
“…Studies have revealed that, although cell replacement has an important role in MSC therapy for some diseases, the ultimate therapeutic effect is predominantly an outcome of immunomodulatary capacity derived from MSCs, which react with immune system [ 4 , 5 ]. This immunomodulatary capacity in MSC therapy primarily presents as immunosuppression in animal models and human studies [ 4 , 6 ]. Based on these two major characteristics, MSCs are potentially useful for tissue repair and regeneration in stem cell therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that ICAM-1 is involved in the regulation of immune responses, mediating cell differentiation and development, and is closely related to lymphocyte homing and recycling. 65 They found that transplantation of ICAM-1overexpressing MSCs not only alleviated colonic inflammation and regulated T cell subpopulations more obviously, but also mediated a higher number of MSCs homing to the colon and spleen of the mouse model of IBD. 64 MicroRNAs are a family of endogenous non-coding RNAs, consisting of 22-24 bp in length.…”
Section: Improves the Efficacy Of Mscsmentioning
confidence: 99%